Corynexochine trilobites of the Harkless Formation and Mule Spring Limestone (Cambrian Series 2, Stage 4), Clayton Ridge, Nevada. (November 2021) - Sundberg, Frederick A.; Webster, Mark
Abstract: Most Cambrian Series 2 faunas of Laurentia are dominated by olenelline trilobites; however, non-olenelline trilobites occur with the olenellines and sometimes dominate the assemblages. Reported here are such non-olenelline trilobites from the Harkless Formation and Mule Spring Limestone at Clayton Ridge, Nevada. At the bottom of the Saline Valley Tongue, Harkless Formation, are two assemblages that are characterized by corynexochines and/or ptychoparioids, with olenellines occurring as only rare components. The corynexochines present in these assemblages include Bonnia cf. B . brennus (Walcott, 1916 ), Ovatoryctocara cf. O . yaxiensis Yuan et al., 2009, Protoryctocephalus ? aff. P .? arcticus Geyer and Peel, 2011, Ogygopsis sp. indet., and Oryctocephalops frischenfeldi Lermontova, 1940 . These assemblages are from the mid-Dyeran Stage, below the lowermost zone in the upper Dyeran ( Arcuolenellus arcuatus Biozone), and can be correlated to Series 2 Stage 4 (Cambrian) assemblages in Greenland, Siberia, and South China based on the corynexochines. Also in the Saline Valley Tongue and the overlying Mule Spring Limestone and lowermost Emigrant Formation are olenelloid-dominated assemblages that contain the corynexochines Bonnia columbensis Resser, 1936, Zacanthopsis aff. Z . levis (Walcott, 1886 ), and Z . sp. indet.